Explaining the Effective Factors on Digital Transformation Strategies in the Telecom Industry of Iran Using the Delphi Method - Jamal Aghayari; Changiz Valmohammadi; Mahmood Alborzi (Discrete Dynamics in Nature and Society)
Digital transformation is emerging as the main driver of widespread change in the world around us. The communications industry is at the forefront of this transformation, both as an industry that is witnessing extensive changes in its market environment and as a major driver of digitalization around the world. The use of technology and the achievements of information technology alone will not lead to digital transformation in the organization because digital transformation is something of a strategy. The purpose of the research is exploratory and the type of applied research. The research method is data analysis, integrated, quantitative, and qualitative. The Delphi method has been used to identify the indicators, and the fuzzy DANP technique has been used to prioritize and affect. In this research, components and indicators of digital evolution have been extracted using qualitative content analysis. For this purpose, library studies including books and articles, structured interviews with industry experts, the content presented in domestic and foreign conferences and lectures, and reference models provided by leading organizations in the industry were used. The components and indicators were approved by the Delphi method, and the relationship between the components and the indicators and their ranking was done using the DANP (DEMTEL-ANP (DANP)) method. In the end, 6 components and 20 indicators were finalized and identified as indicators of high importance.